Giant cervical fibroid in a perimenopausal women: a rare case report - K., Jaya Rakini; Ravichandran, Vidhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Uterine leiomyomas, are smooth muscle neoplasms and the most common benign gynaecological tumour prevailing in 70-80% of women reaching 50 years. Fibroids contribute to 40-60% of hysterectomies performed all over the world. Most of the fibroids are situated in the body of the uterus, but only 1 to 2% of cases, they are confined to cervix. Most of the patients remain asymptomatic but in patients with large fibroids mostly present with pressure symptoms depends upon location of fibroid. Cervical leiomyoma is mostly single and are subserous or interstitial in origin. They arise either from vaginal or supra-vaginal portion of cervix. We report a case of cervical fibroid in perimenopausal parous women with anaemia proceeded with laparotomy after anaemia correction. It showed a huge fibroid arising from the posterior cervix with uterus pushed anteriorly. Enucleation followed by abdominal hysterectomy was done. Large cervical fibroids are rare, presenting with surgical difficulties. Careful dissection by expert hands is needed in the management of such cases. Patient had an uneventful post-operative recovery.